FToeplitz ve Hemen Hemen FHankel Matrislerinin Normları için Sınırlar - TAŞKARA, Necati; YALÇINER, Aynur; KÖSE, Hasan (My University, 2003)
Bu çalışmada, FToeplitz ve Hemen Hemen FHankel matrislerini tanımlayarak bu matrislerin Euclides normları için üst sınırlar elde edildi
On the Bounds for the Norms of FToeplitz and Almost FHankel Matrices
In this study, we obtain defined Ftoeplitz and Almost Fhankel matrices. Then, we obtained upper bounds for the Euclidean norm of these matrices.
Keywords: Norm, FToeplitz, FHankel, Euclidean Norm